Pengaruh Model Pembelajaran Talking Stick terhadap Keaktifan Belajar Siswa pada Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti Kelas VIII di SMP Negeri 1 Balige Kabupaten Toba Tahun Pembelajaran 2024/2025 - Hisar R. Panjaitan; Dame Taruli Simamora; Baginda Sitompul; Senida Harefa; Robert K.A. Simangunsong (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The purpose of this study was to determine the effect of the Talking Stick Learning Model on Student Learning Activity in the Subject of Christian Religious Education and Character Education for class VIII at SMP Negeri 1 Balige, Toba Regency in the 2024/2025 Academic Year. The research hypothesis is: